BEBERAPA MACAM CACAT TUBUH YANG TERJADI PADA BENIH IKAN KERAPU CANTANG HASIL HATCHERY - Ismi, Suko (JFMR (Journal of Fisheries and Marine Research), 2020)
Cantang grouper is a hybrid between female tiger grouper (Epinephelus fuscoguttatus) and male giant grouper (Epinephelus lanceolatus) cantang grouper is currently in big demand for aquaculture because it has fast growth. Seed requirement of this fish can be supplied from hatcheries production, one of the constraints of the hatchery production it is deformities. The purpose of this study is to know the kinds of deformities that occur in fish seeds produced from the hatchery. The study was conducted in  Gerokgak District , Buleleng Regency, Bali. Data obtained by survey and direct observation in several hatcheries and  collected was analyzed descriptively. The results showed that highest deformity were open gills reached 90.1%, followed by deformity of tail  72.6%, head and mouth  reached 23.8% and backbone (kiposis, lordosis skiolosis) reached 20.8%. High deformities in the resulting seed will result in losses to the hatchery because the seed can't sell.